OPTIMIZATION OF COMPRESSION MOULDING PARAMETERS FOR MULTI FILLER POLYMER COMPOSITE USING TAGUCHI METHOD - Jamil, N.A.; Selamat, M.Z.; Hasan, R.; Daud, M.A.M.; Tahir, M.M. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Polymer Electrolyte Membrane Fuel Cells (PEMFC) performance depends on the properties of bipolar plates (BP). In order to produce the best performance of BP, compression moulding parameters need to be optimized. This study determined the compression moulding parameters of Graphite (G) / Carbon Black (CB) / Carbon Fiber (CF) / Polypropylene (PP) composites using Taguchi method (TM) in order to optimize the properties of BP plate. L9 Orthogonal Array with four factors and three levels was chosen as a design of experiment for G/CB/CF/PP composition with a weight percentage of 50/25/5/20. The factors selected for this study were heating temperature, load, preheating pressing time and pressing time. The electrical conductivity value of each sample was analyzed by signal to noise ratio using TM with the larger-the-better condition in order to determine the optimum parameters. Confirmation experiment was conducted to validate the optimum parameters obtained from the TM. The electrical conductivity result of G/CB/CF/PP composites for confirmation experiment was 393.49 S/cm and it was higher than nine trials and the TM predicted value. Hence, the optimum parameters of compression moulding can be obtained using TM to improve the electrical conductivity of G/CB/CF/PP composites. TM is an effective way to get the optimal moulding parameters for G/CB/CF/PP composites and is very useful to fabricate bipolar plate for PEMFC.